World watch Geography skills book 1 grade 6 - Moorcroft, Christine (Karachi : Oxford university press, 2023)
The "World Watch Geography Grade 6 Skills Book" is designed to help students develop essential geographic skills and knowledge in a more interactive and practical way. This supplementary book focuses on building the necessary skills that students need to understand and analyze geographical information. It typically includes activities and exercises that help reinforce the concepts introduced in the main geography textbook.
Keywords: Geography : Skills book; Oxford : Grade 6